MANAJEMEN LABA MELALUI TRANSAKSI PIHAK ISTIMEWA DI SEKITAR PENAWARAN SAHAM PERDANA - Ridha Yani Herman; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
Publishing of the prospectus is expected to provide investors with a relevant information before investing and used to assess company that will go public. The limited information sourced from prospectus that owned by investor regarding condition of company will lead to information asymmetry. This condition is used by managers to perform earnings management. The purpose of this study is to examine the influence of related party transaction about earnings management in periode before initial public offering (IPO). The population of this study is 38 samples from non-financial firms that conduct IPO’s in the Indonesia Stocked Exchange in 2001 to 2011. The sampling method used for this study is purposive sampling. Paired Sample t-test is used to examine whether significant earnings management which is proxied by ROA among the firm sample for t-1, t=0, and t+1 around the IPO and multiple linear regression is used to RP Sales, RP Purchases, and firm size to effect of earnings management. The result of this study has established that significant changes between ROAt=0 with ROAt-1 IPO period, the related party sales transaction (RP Sales) and firm size significant positive effect of earnings management. However, this study indicate that the related party purchases transaction (RP Purchases) do not has a significant effect of earnings management.